Temporal and spatial variation in otter Lutra lutra diet in Northern Ireland - Preston, Sarah; Portig, Alexander; Montgomery, Ian; McDonald, Robbie; Dick, J.T.A.; Fairley, J.S. (2007)
The European otter (Lutra lutra L.) has a highly specialised diet that is composed predominantly of fish. The current study investigates the percentage composition of food items in otter spraints collected in six river catchments in Northern Ireland in 1980 and again from the same locations in 2003. Spraints contained significantly more salmonids than any other prey item. The composition of spraints differed among catchments. More salmonids and three-spined stickleback (Gasterosteus aculeatus L.) were found in spraints from the Glens of Antrim, while spraints from the Lagan catchment had significantly more eel (Anguilla anguilla L.). There were significantly more spraints containing non-fish food items in 2003 compared with 1980. These non-fish items were insects, amphipods, birds, rats (Rattus norvegicus Berkenhout) and lagomorphs. Increased consumption of non-fish items was apparent in all but one of the river catchments. The mean diversity of spraint composition was significantly greater in 2003 than in 1980. Therefore, our findings indicate that otters have diversified their diet since 1980 and now eat more non-fish prey.